Efficient and sustainable extraction of uranium from aquatic solution using biowaste-derived active carbon - Ahmad, Ashfaq; Khan, Salah Ud-Din; Khan, Rawaiz; Haneklaus, Nils (Frontiers in Chemistry, 2023)
Efficient and cost-effective biosorbents derived from biowaste are highly demanding to handle various environmental challenges, and demonstrate the remarkable synergy between sustainability and innovation. In this study, the extraction of uranium U(VI) was investigated on biowaste activated carbon (BAC) obtained by chemical activation (phosphoric acid) using Albizia Lebbeck pods as biowaste. The biowaste powder (BP), biowaste charcoal (BC) and BAC were evaluated by thermogravimetric analysis (TGA), Fourier transform infrared spectroscopy (FTIR) and Brunauer-Emmett-Teller (BET) with nitrogen adsorption for thermal properties, chemical structures, porosity and surface area, respectively. The pHPZC for acidic or basic nature of the surface and X-ray diffraction (XRD) analysis were performed for BAC. The morphological and elemental analysis were performed by scanning electron microscopy (SEM) and energy dispersive X-ray (EDX). The extraction of uranium U(VI) ions from aqueous solutions using BAC as sorbent was investigated by using different variables such as pH, contact time, initial uranium U(VI) concentration and BAC dose. The highest adsorption (90.60% was achieved at 0.5 g BAC dose, 2 h contact time, pH 6, 10 ppm initial U(VI) concentration and with 200 rpm shaking speeds. The production of this efficient adsorbent from biowaste could be a potential step forward in adsorption of uranium to meet the high demand of uranium for nuclear energy applications.